Study of key amino acid residues of GH66 dextranase for producing high-degree polymerized isomaltooligosaccharides and improving of thermostability - Lin, Qianru; Wang, Huanyu; Xu, Yingying; Dong, Dongxue; Miao, Qingzhen; Lu, Jing; Lyu, Mingsheng; Wang, Shujun (Frontiers in Bioengineering and Biotechnology, 2022)
Obtaining high-degree polymerized isomaltose is more difficult while achieving better probiotic effects. We investigated the mutation specificity and enzymatic properties of SP5-Badex, a dextranase from the GH66 family, and determined its mutation sites through molecular docking to obtain five mutants, namely E454K, E454G, Y539F, N369F, and Y153N. Among them, Y539F and Y153N exhibited no enzymatic activity, but their hydrolysates included isomaltooligosaccharides (IMO4). The enzymatic activity of E454G was 1.96 U/mL, which was 3.08 times higher than that before mutation. Moreover, 70% of the enzymatic activity could be retained after holding at 45 ℃ for 180 min, which was 40% higher than that of SP5-Badex. Furthermore, its IMO4 content was 5.62% higher than that of SP5-Badex after hydrolysis at 30 ℃ for 180 min. To investigate the effect of different amino acids on the same mutation site, saturation mutation was induced at site Y153, and the results showed that the enzyme activity of Y153W could be increased by 2 times, and some of the enzyme activity could still be retained at 50 ℃. Moreover, the enzyme activity increased by 50% compared with that of SP5-Badex after holding at 45 ℃ for 180 min, and the IMO4 content of Y153W was approximately 64.97% after hydrolysis at 30 ℃ for 180 min, which increased by approximately 12.47% compared with that of SP5-Badex. This site is hypothesized to rigidly bind to nonpolar (hydrophobic) amino acids to improve the stability of the protein structure, which in turn improves the thermal stability and simultaneously increases the IMO4 yield.